The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnagi.2021.782082
|View full text |Cite
|
Sign up to set email alerts
|

The Gut–Brain Axis and Its Relation to Parkinson’s Disease: A Review

Abstract: Parkinson’s disease is a chronic neurodegenerative disease characterized by the accumulation of misfolded alpha-synuclein protein (Lewy bodies) in dopaminergic neurons of the substantia nigra and other related circuitry, which contribute to the development of both motor (bradykinesia, tremors, stiffness, abnormal gait) and non-motor symptoms (gastrointestinal issues, urinogenital complications, olfaction dysfunction, cognitive impairment). Despite tremendous progress in the field, the exact pathways and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 179 publications
(190 reference statements)
0
55
0
Order By: Relevance
“…There are numerous different pathways by which the gut could contribute to PD and in this study, we evaluated the contribution of intestinal hyperpermeability to the PD-like phenotype based on the following rationale: (1) data from our group has demonstrated intestinal hyperpermeability is observed in PD patients ( 8 , 76 , 77 ), (2) numerous conditions that may be risk factors for PD (e.g., diabetes, ulcerative colitis) are associated with intestinal hyperpermeability ( 78 , 79 ), and (3) intestinal hyperpermeability is associated with increased systemic inflammation which may drive neuroinflammation in PD ( 80 , 81 ). Thus, the rationale behind this study was to investigate if increased intestinal permeability could promote neuroinflammation and exacerbate the PD phenotype in ASO mice through a mechanism including intestinal and/or systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous different pathways by which the gut could contribute to PD and in this study, we evaluated the contribution of intestinal hyperpermeability to the PD-like phenotype based on the following rationale: (1) data from our group has demonstrated intestinal hyperpermeability is observed in PD patients ( 8 , 76 , 77 ), (2) numerous conditions that may be risk factors for PD (e.g., diabetes, ulcerative colitis) are associated with intestinal hyperpermeability ( 78 , 79 ), and (3) intestinal hyperpermeability is associated with increased systemic inflammation which may drive neuroinflammation in PD ( 80 , 81 ). Thus, the rationale behind this study was to investigate if increased intestinal permeability could promote neuroinflammation and exacerbate the PD phenotype in ASO mice through a mechanism including intestinal and/or systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the 2000s, human postmortem studies led by Braak and colleagues suggested for the first time that such α-Syn pathology is not confined to the CNS and is also detectable in the ENS [56][57][58], which is a division of the peripheral nervous system that controls the gastrointestinal system [59]. The evidence of α-Syn pathology also in this system lent support to the theory that PD pathology could be initiated in the ENS [36] and that it could be spread from the gastrointestinal tract to the midbrain via the vagus nerve, resulting in the selective death of SNc dopamine neurons [57,60] (see Figure 1).…”
Section: Current Evidence On the Gut-brain Hypothesis Of Parkinson's ...mentioning
confidence: 96%
“…This pro-inflammatory status detected in DJ1 deficiency may also be mediated by gut microbiome dysregulation, thus altering the so-called gut–brain axis whose dysfunction is widely involved in the pathophysiology of PD [ 5 ]. Notably, DJ1 knock-out mice presented a significantly higher production of fecal calprotectin and monocyte chemotactic protein 1 (MCP-1), along with both serum and fecal higher levels of malonate [ 52 ], which can mediate the degeneration of dopaminergic neurons [ 53 ].…”
Section: Dj1mentioning
confidence: 99%
“…Notwithstanding, the connection between CNS and the periphery is also mediated by the strict connection between the gut and the brain, with the so-called gut–brain axis. Through this bidirectional pathway, toxins and cytokines produced by a dysregulated gut microbioma can reach the CNS either directly through the vagus nerve, or indirectly with the blood circulation where they are released as a consequence of microbial translocation due to augmented intestinal permeability [ 5 ].…”
Section: Introductionmentioning
confidence: 99%